Association between follicular fluid phthalate concentrations and extracellular vesicle microRNAs expression. Issue 6 (22nd April 2021) - Barnett-Itzhaki, Zohar; Knapp, Sarah; Avraham, Chaya; Racowsky, Catherine; Hauser, Russ; Bollati, Valentina; Baccarelli, Andrea A; Machtinger, Ronit
Abstract: STUDY QUESTION: Are phthalate metabolite concentrations in follicular fluid (FF) associated with the expression of extracellular vesicle microRNAs (EV-miRNAs)? SUMMARY ANSWER: Phthalate metabolite concentrations are associated with the expression of EV-miRNA and their associated pathways in FFs. WHAT IS KNOWN ALREADY: Phthalate metabolites were recently detected in FF. Urinary phthalate metabolite concentrations alter the expression of EV-miRNAs in FF. STUDY DESIGN, SIZE, DURATION: Prospective study including 105 women recruited between January 2014 and August 2016 in a tertiary university-affiliated hospital. PARTICIPANTS/MATERIALS, SETTING, METHODS: We assessed FF concentrations of 12 phthalate metabolites. EV-miRNAs were isolated from aliquots of the same FF, and their expression profiles were measured using a human miRNA panel. Associations between EV-miRNAs that were present in >50% of the samples and phthalate metabolites that were measured in >74% of the FF samples were tested. Genes regulated by EV-miRNAs that were found to be significantly (false discovery rate q -value < 0.1) correlated with FF-phthalates were analyzed for pathways linked with female fertility using miRWalk2.0 Targetscan database, DAVID Bioinformatics Resources and Kyoto Encyclopedia of Genes and Genomes (KEGG). MAIN RESULTS AND THE ROLE OF CHANCE: Of 12 phthalate metabolites, 11 were measured in at least one FF sample. Mono (6-COOH-2-methylheptyl) phthalate (MCOMHP), mono-2-ethyl-5-carboxypentyl phthalate (mECPP), mono-n-butyl phthalate (MnBP), monobenzyl phthalate (MBzP), mono-isobutyl phthalate (MiBP), monoethyl phthalate (MEP) and mono (7-COOH-2-methyloctyl) phthalate (MCOMOP) were detected in more than 74% of the samples. Of 754 EV-miRNAs tested, 39 were significantly associated either with MEP, MBzP, MCOMOP, MCOMHP and/or with mECPP, after adjusting for multiple testing ( P < 0.05). KEGG-based pathway enrichment analysis of the genes regulated by these miRNAs showed that these EV-miRNAs may be involved in pathways related to ovary or oocyte development, maturation and fertilization. LIMITATIONS, REASONS FOR CAUTION: The use of miRNA panel array limits the number of potential relevant miRNAs. Moreover, several of the phthalate metabolites examined may be biased due to internal (enzymatic activity) or external (contamination in medical interventions) causes. WIDER IMPLICATIONS OF THE FINDINGS: Phthalate metabolites may alter follicular EV-miRNAs profile and thus impair pathways that are involved with oocyte development, maturation and fertilization. Our results contribute to understanding of possible mechanism(s) in which endocrine disruptor chemicals interfere with female fertility. STUDY FUNDING/COMPETING INTERESTS: This work was supported by the National Institutes of Environmental Health Sciences [Grant R21-ES024236]; and Environmental Health Fund, Israel [Grant 1301], no competing interests. TRIAL REGISTRATION NUMBER: N/A.